2019
DOI: 10.1111/cei.13306
|View full text |Cite
|
Sign up to set email alerts
|

Patients with tumour necrosis factor (TNF) receptor-associated periodic syndrome (TRAPS) are hypersensitive to Toll-like receptor 9 stimulation

Abstract: Summary Tumour necrosis factor receptor‐associated periodic syndrome (TRAPS) is a hereditary autoinflammatory disorder characterized by recurrent episodes of fever and inflammation. It is associated with autosomal dominant mutations in TNFRSF1A, which encodes tumour necrosis factor receptor 1 (TNF‐R1). Our aim was to understand the influence of TRAPS mutations on the response to stimulation of the pattern recognition Toll‐like receptor (TLR)‐9. Peripheral blood mononuclear cells (PBMCs) and serum were isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Considering these findings, TRAPS mutations are likely to lower the threshold of inflammatory responses to various TLR ligands, including pathogen‐associated molecular patterns and damage‐associated molecular patterns. Indeed, a recent study has reported that PBMCs from TRAPS patients are susceptible to a TLR‐9 ligand . Apart from TLR ligands, heparin has been suggested to be a natural stimulant of inflammation , which might imply the possible involvement of the transmembrane protein 184A, a receptor for heparin .…”
Section: Discussionmentioning
confidence: 99%
“…Considering these findings, TRAPS mutations are likely to lower the threshold of inflammatory responses to various TLR ligands, including pathogen‐associated molecular patterns and damage‐associated molecular patterns. Indeed, a recent study has reported that PBMCs from TRAPS patients are susceptible to a TLR‐9 ligand . Apart from TLR ligands, heparin has been suggested to be a natural stimulant of inflammation , which might imply the possible involvement of the transmembrane protein 184A, a receptor for heparin .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TLR-9 activation of PBMCs from a patient carrying the p.C62Y (C33Y) mutation triggered production of many pro-inflammatory cytokines and activated several inflammatory pathways, including NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells), JNK (c-Jun N-terminal kinase), and P38 MAPK. Collectively, these data demonstrate hyperactivity of the innate immune reponse in TRAPS patients [41].…”
Section: Pathophysiology In Trapsmentioning
confidence: 62%
“…Some of these signalling patterns contribute to the activation of the adaptive immune system [66]. Therefore, it is understandable that abnormalities of the TLRs pathway are linked to autoinflammation [67] and autoimmunity [68]. Notably, regulation of TLR activation may be used to treat inflammatory conditions.…”
Section: Cellular Components Of the Innate Immune Systemmentioning
confidence: 99%
“…HCQ inhibition of TLR-7 is considered particularly significant for ameliorating SLE disease and anti-RO/SSA antibody-mediated congenital heart block [69], whereas hypersensitivity to TLR-9 was acknowledged in TNF receptor-associated periodic syndrome. This hereditary autoinflammatory disorder is characterized by recurrent episodes of fever and inflammation and autosomal dominant mutations in the TNFRSF1A gene [67]. A role for TLR-4 was suggested in the pathogenesis of ‘deficiency of IL-36Ra’ (DITRA), a systemic autoinflammatory disease that includes generalized pustular psoriatic fever and systemic symptoms [70]…”
Section: Cellular Components Of the Innate Immune Systemmentioning
confidence: 99%